Room‐Temperature Spray Deposition of Large‐Area SnO2 Electron Transport Layer for High Performance, Stable FAPbI3‐Based Perovskite Solar Cells. Issue 2 (11th December 2021) - Kumar, Neetesh; Lee, Hock Beng; Sahani, Rishabh; Tyagi, Barkha; Cho, Sinyoung; Lee, Jong‐Soo; Kang, Jae‐Wook
Abstract: The performance and scalability of perovskite solar cells (PSCs) is highly dependent on the morphology and charge selectivity of the electron transport layer (ETL). This work demonstrates a high‐speed (1800 mm min −1 ), room‐temperature (25 °C–30 °C) deposition of large‐area (62.5 cm 2 ) tin oxide films using a multi‐pass spray deposition technique. The spray‐deposited SnO2 (spray‐SnO2 ) films exhibit a controllable thickness, a unique granulate morphology and high transmittance (≈85% at 550 nm). The performance of the PSC based on spray‐SnO2 ETL and formamidinium lead iodide (FAPbI3 )‐based perovskite is highly consistent and reproducible, achieving a maximum efficiency of ≈20.1% at an active area ( A ) of 0.096 cm 2 . Characterization results reveal that the efficiency improvement originates from the granular morphology of spray‐SnO2 and high conversion rate of PbI2 in the perovskite. More importantly, spray‐SnO2 films are highly scalable and able to reduce the efficiency roll‐off that comes with the increase in contact‐area between SnO2 and perovskite film. Based on the spray‐SnO2 ETL, large‐area PSC ( A  = 1.0 cm 2 ) achieves an efficiency of ≈18.9%. Furthermore, spray‐SnO2 ETL based PSCs also exhibit higher storage stability compared to the spin‐SnO2 based PSCs. Abstract : Spray deposited SnO2 (spray‐SnO2 ) film enables a power conversion efficiency (PCE) of 20.1% for FAPbI3 ‐based perovskite solar cells (PSCs). The PSCs based on large‐area (62.5 cm 2 ) spray‐SnO2 films deposited on multiple substrates (S1–S10) display highly consistent PCE, manifesting its scalability potential.